Teachers’ assessment literacy improves teaching efficacy: A view from conservation of resources theory - Wang, Hongxi; Sun, Wenwen; Zhou, Yue; Li, Tingting; Zhou, Peiling (Frontiers in Psychology, 2022)
Recent revisions to the Conservation of Resources theory have not only reclassified categories of resources, but have also acknowledged the conceptual importance of “gain spirals” and “resource caravans” in enriching the theoretical understanding of resources. Given that teachers’ assessment literacy is a prominent yet underexplored personal constructive resource in teaching, this paper examines its role in teaching efficacy. In addition, personal energy resources (e.g., psychological capital and professional identity) are studied as antecedents to teaching efficacy. To this end, a survey based on the Chinese versions of the Teacher Assessment Literacy Scale, the Teaching Efficacy Scale, the Psychological Capital Scale, and the Teacher Professional Identity Scale was administered to secondary school teachers in Henan Province, China, and 351 completed, valid surveys were returned. The findings indicated that the teachers’ assessment literacy and teaching efficacy were positively correlated, verifying that assessment literacy can influence teaching efficacy through the separate and chain mediation effects of psychological capital and professional identity. The identification of such mediating pathways has confirmed that resources owned by teachers can lead to gain spirals and full resource caravans, thus expanding the Conservation of Resources theory by positing that resources can be nested within one another. This study has theoretical implications for teaching efficacy research and the Conservation of Resources theory as well as practical implications regarding how to boost teachers’ constructive and energy resources and professional development.